Generic skills level of bachelor of vocational education students University Tun Hussein Malaysia - Tukiran, Nor Anis Intan Aqiah; Ahmad Badri, Nur ‘Izzah (Penerbit UTHM, 2021)
The development of a country can be enhanced by the presence of human skills. The direction or goal of a country's development is the main thrust of human capital development which is the most accurate injection of the application of generic skills. According to Mohamed (2014), Malaysia needs to compete with other countries to produce successful human capital. Ministry of Education Malaysia Plan 2015-2025 (Higher Education Report) Vocational College is one of the leading providers of TVET higher education to develop skills to supply skilled TVET workers by 2020.